DHOHIROTU AL-TAGYIR AL-LUGHOWI FIL LUGHOTIL ‘ARABIYAH - Dimyati, Muhammad Afifuddin (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2009)
In sociolinguistic study, interesting phenomena to be discussed in Arabic language is Al-taghyyur al-lughowi (linguistic change), mainly the language change in Arabic language it its historical course in line with its dynamic and as the result of the interaction with other languages. This paper analyze the phenomena of language change in Arabic language comprehensively by emphasizing on the causes of the Arabic language change and the types or forms of the changes at the phonetic, morphology, syntax, semantic and lexical all of which are followed by some of the examples. This study will be useful for the learners in understanding some common characteristics of Arabic language so that it is easier for them to use and practice the language to improve their language capability